Anesthetic-Induced Intraoperative Dream Associated With Remission of a Psychiatric Disorder: A Case Report. Issue 8 (10th August 2022) - Chow, Harrison S.; Hack, Laura M.; Kawai, Makoto; Heifets, Boris D.
Abstract : Trauma is associated with debilitating acute and posttraumatic stress disorders, which have limited treatment options. We report on a patient undergoing surgical hand repair after a recent knife attack who experienced vivid dreaming and subsequent remission of acute stress disorder. After local anesthesia with propofol sedation she recalled a dream wherein she relived the attack, sought medical care, completed surgery, and returned home with a healed hand. While intraoperative dreaming is common, this case details potential associations between anesthetic state, dreaming, intraoperative electroencephalography, and remission of a psychiatric disorder. Our experience suggests a novel intervention for stress disorders.